2020
DOI: 10.1177/0218492320974184
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal thoracoscopic surgical management using a suture traction for primary pneumothorax

Abstract: Background We devised a new strategy using suture traction to facilitate the management of primary spontaneous pneumothorax during uniportal thoracoscopy. To test its validity, we compared the outcomes of our modified technique with those of conventional three-port thoracoscopy. Methods This retrospective study included all 43 consecutive patients with primary spontaneous pneumothorax undergoing thoracoscopy between January 2017 and December 2019. They were divided within two groups: uniportal thoracoscopy usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…2,15 Recently, uniportal VATS has broadened its application in lung bullectomy, pulmonary wedging, lobectomy and segmentectomy due to less-invasiveness such as less pain and cosmetic reasons over multiportal VATS. 4,16,17 Unlike lung bullectomy and pulmonary wedging, radical resection of NSCLC needs to cut off blood vessels and airways, which may induce bleeding and air leakage postoperatively, even though these may have been preliminarily examined and solved during surgery. 18 In addition, systematic dissection of the lymph nodes could be related to increased leakage of lymph fluid, and there is a reasonable chance of chylothorax after pulmonary resection, which may lead to pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,15 Recently, uniportal VATS has broadened its application in lung bullectomy, pulmonary wedging, lobectomy and segmentectomy due to less-invasiveness such as less pain and cosmetic reasons over multiportal VATS. 4,16,17 Unlike lung bullectomy and pulmonary wedging, radical resection of NSCLC needs to cut off blood vessels and airways, which may induce bleeding and air leakage postoperatively, even though these may have been preliminarily examined and solved during surgery. 18 In addition, systematic dissection of the lymph nodes could be related to increased leakage of lymph fluid, and there is a reasonable chance of chylothorax after pulmonary resection, which may lead to pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…VATS lobectomy was first introduced in 1992, 14 since when it has been increasingly performed as an alternative to thoracotomy due to the minimally invasive nature of the procedure and its many superiorities 2,15 . Recently, uniportal VATS has broadened its application in lung bullectomy, pulmonary wedging, lobectomy and segmentectomy due to less‐invasiveness such as less pain and cosmetic reasons over multiportal VATS 4,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate for patients treated conservatively alone is approximately 32% 10 . VATS bullectomy is considered the gold standard treatment for controlling pneumothorax in patients with PSP 11 . However, recurrence rates following bullectomy alone remain relatively high.…”
Section: Discussionmentioning
confidence: 99%
“… 10 VATS bullectomy is considered the gold standard treatment for controlling pneumothorax in patients with PSP. 11 However, recurrence rates following bullectomy alone remain relatively high. In a randomized controlled trial reported by Min et al in 2014, 12 the recurrence rate after bullectomy alone was 7.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the most frequent causes of air leaks in pulmonary surgery are pleural alveolar fistulas, while BPF often require surgical intervention and have various risk factors. After pulmonary resection, air leakage is frequently right after surgery in about 60% of cases; however, most air leaks resolve within 48 h, although some will persist; 3,4 when the air leak lasts more than 5 days it is defined as a prolonged air leak; however, a fair heterogeneity of definitions is reported in the literature, and some authors use 7 days (or longer) as cutoff. Persistent air leaks (PAL) are reported with an incidence of 4%–16% 5 .…”
Section: Introductionmentioning
confidence: 99%